Cloud-based emaintenance solutions for condition-based maintenance of wheels in heavy haul operation - Karim, Ramin; Birk, Wolfgang; Larsson-Kråik, Per-Olof (Luleå tekniska universitet, Drift, underhåll och akustik, 2015)
The Swedish ore line, began in 1898 and was completed and operational by 1902. The line was later electrified and remains so to this day. A study on wheel-rail interaction, to optimize wheel and rail profiles on the Malmbanan and Ofoten lines states that there is a need to develop and apply limit values for the allowable length of single and multiple cracks on wheels. Herein, all stakeholders in the railway organization have to be involved. Provisioning of an integrated decision support system for track and vehicle contributes to increased efficiency and improved effectiveness of the maintenance process, which in turn enables achievement of business excellence. However, an integrated decision support process for maintenance is highly dependent on appropriate information logistics which enables information provisioning to various maintenance stakeholders. One emerging approach for development of eMaintenance solutions is utilization of cloud-based technologies. Cloud-based eMaintenance solutions promises smooth information logistics for maintenance decision support. Hence, the purpose of this paper is to propose an approach for condition-based maintenance decision-making relating to railway vehicle wheels, based on a cloud-based eMaintenance solution. The paper also demonstrates how the proposed approach can be implemented for estimation of Remaining Useful Life (RUL) of railway vehicle wheels. Godkänd; 2015; 20150517 (raka)